Silencing of Bmi-1 Gene Enhances Chemotherapy Sensitivity in Human Glioblastoma Cells - Hong, Yang (Med Sci Monit, 2015)
BACKGROUND: The aim of this study was to determine the influence of the BMI1 gene on chemotherapy sensitivity in human glioma cells. MATERIAL/METHODS: The expression of the BMI1 gene in 41 cases of human brain glioma was determined by quantitative real-time PCR. The silencing effect of RNA interference on the BMI1 gene was detected by Western blot. Methyl thiazolyl tetrazolium assay (MTT) and flow cytometry methods were used to determine the cell viability and apoptosis rate of the U251 cells with BMI1 silencing. After those U251 cells were treated with Cisplatin (DDP), the cell viability and apoptosis rate were further detected. RESULTS: The BMI1 mRNA in glioma was remarkably up-regulated, 176.3% as much as that in peri-cancerous tissues (P<0.05). The siRNA-BMI1 significantly and effectually inhibited the expression of BMI1 protein (P<0.05). The cell viability decreased in U251 cells with BMI1 silenced, and the apoptosis rate upgraded significantly (P<0.05 for both). After treating with DDP at various concentrations (1, 3, and 5 μg/ml), the cell viability in the BMI1-slienced U251 cells was much lower than that in corresponding control U251 cells at each DDP concentration (P<0.05 for all), and the apoptosis rate showed the opposite changing trends (P<0.05 for all). CONCLUSIONS: There is a notable relationship between the over-expression of BMI1 and the carcinogenesis of gliomas. The silence of BMI1 inhibited cell proliferation and enhanced the apoptosis of the U251 cells, and increased the chemotherapy sensitivity of U251 cells to DDP.